Deutsch-hebräische Symbiose: zur Poetologie der Selbstübersetzung in Manfred Winklers Kafka-Adaptionen - Kühne, Jan (Naharaim, 2025)
This paper investigates the poetics of self-translation in the bilingual oeuvre of Manfred Winkler (1922-2014), an Israeli poet from the Bukovina, writing in both German and Hebrew. At the heart of the analysis lies Winkler’s poetological concept of a "symbiosis" between German and Hebrew, which serves as a point of departure for examining the tension between German-speaking Jewish heritage and Zionist Hebraism in his translingual work. Focusing on Winkler's German and Hebrew adaptations of Kafka's  Metamorphosis , the article demonstrates how lyrical self-translation enacts the transformation of the self as a dialogical process of translingual creativity and poetic evolution. Building on the botanical metaphors found in Winkler's theoretical reflections, the study proposes a model of autogamous and allogamous translingualism - distinguishing between different modes of poetic self-translation, from internal variation to external inspiration.